U.S. Business Schools’ Expansion to The Global Market: Positioning Strategy and Market Competition - Cao, Yong; Zhang, Lei (Archives of Business Research, 2023)
In the last decade, higher education institutions in the United States have experienced an increasing trend of internationalization, more and more universities have been aggressively recruiting international students. The enrollment of international students in US Universities has increased from 564,766 in the year 2004-2005 to 974,926 in the year 2014-2015, a 72.3 % increase in ten years. Due to COVID, there were 1.25 million international students studying in the US last year. This is 17.86 percent lower than the 2019-2020 academic year (data from the Student and Exchange Visitor Program (SEVP). Business schools in the United State stand on the frontier of internationalization. Some universities even have started to build satellite campuses and programs in other countries. Examples include Duke University built its campus in Kunshan China, and NYU built its campus in Shanghai, China. Based on the information provided by the Institute of International Education (iie.org), business and management programs have been continually ranked as number one in international student enrollment. Of the 974,926 international students enrolled in high education institutions in the United States in 2014-2015, 20.2% of them enrolled in Business and Management programs, with a total number of 197,258 students. In the years of 2020, the number of international students in USA business and management programs is 174,470, a slight drop from previous years due to COVID-19. In the United States, there are more than two thousand business schools, of which five hundred and fifteen (515) are accredited by the Association to Advance Collegiate Schools of Business (AACSB International). Each of these schools has a different ownership entity, either a private university or a public-owned university. In addition, each of them has different brand name recognition by the students, parents, and peers as well. Some schools’ brand names are highly recognized in the market, while others may not be well known at all. What are the appropriate strategies when these schools internationalize their program? In this paper, we propose a two-factor model, using ownership entity and brand name recognition as to conduct a taxonomy of US business schools. We classify business schools into four groups and further propose different positioning strategies for the four groups. Our research contributes to the literature on the internationalization of business programs in several ways. First, our two factors classification system for the business schools results in four groups of business school types, each of which has its unique supporting resources, academic reputations, and entity ownership structure. We further provide different positioning strategies for each type of school and college. The positioning strategies and the associated curriculum design as well as the supporting resources will then serve as a competition tool to attract future international students. Finally, our framework could provide guidance for the business school deans and the other university administrators for their action formulation.